2022
DOI: 10.3390/jcm11237236
|View full text |Cite
|
Sign up to set email alerts
|

Starting Home Telemonitoring and Oxygen Therapy Directly after Emergency Department Assessment Appears to Be Safe in COVID-19 Patients

Abstract: Background: Since data on the safety and effectiveness of home telemonitoring and oxygen therapy started directly after Emergency Department (ED) assessment in COVID-19 patients are sparse but could have many advantages, we evaluated these parameters in this study. Methods: All COVID-19 patients ≥18 years eligible for receiving home telemonitoring (November 2020-February 2022, Albert Schweitzer hospital, the Netherlands) were included: patients started directly after ED assessment (ED group) or after hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Further, van Herwerden et al showed in 49 patients, that, although 6 patients required readmission, home telemonitoring and oxygen administration can be safely applied in COVID-19 patients [20]. Very interestingly, another study comparing home telemonitoring and oxygen therapy started directly after emergency department (ED) vs. hospital admission, concluded that starting home telemonitoring and oxygen therapy directly after ED assessment was safe [21], with a total home telemonitoring duration of 14 days in both groups.…”
Section: Safety Of Early Return Home In Patients Hospitalized For Cov...mentioning
confidence: 99%
“…Further, van Herwerden et al showed in 49 patients, that, although 6 patients required readmission, home telemonitoring and oxygen administration can be safely applied in COVID-19 patients [20]. Very interestingly, another study comparing home telemonitoring and oxygen therapy started directly after emergency department (ED) vs. hospital admission, concluded that starting home telemonitoring and oxygen therapy directly after ED assessment was safe [21], with a total home telemonitoring duration of 14 days in both groups.…”
Section: Safety Of Early Return Home In Patients Hospitalized For Cov...mentioning
confidence: 99%